Parkin and its molecular associations in gliomas - a systematic review - Eduardo Morais de Castro; Leonardo Vinícius Barbosa; João Vitor Alves Ferreira; Diancarlos Pereira de Andrade; Rosiane Guetter Mello; Luiz Fernando Bleggi Torres; Lucia de Noronha; Cleber Machado-Souza (BMC, 2021)
Abstract Parkin, a protein encoded by PRKN, discovered in the context of Parkinson's disease, controls proteasomal degradation by protein ubiquitination and acts on cell cycle control and mitochondrial homeostasis, among other cellular processes. Parkin has been also implicated in several carcinomas, melanoma and leukemia. In the neoplastic setting, reduced parkin level usually indicates poorer prognosis. Some authors have described the associations between parkin and gliomas. Gliomas are a heterogeneous group of tumors that arise in the central nervous system, astrocytomas being the most common. The aim of this systematic review is to evaluate how parkin behaves in gliomas and the molecular pathways associated in this interaction. A search was conducted in PubMed, EBSCO and Scopus and 8 published articles were identified as eligible studies. The studies were categorized in three groups, according to their main emphasis: PRKN mutation patterns detected in gliomas, parkin effects on tumor growth and survival rates, and molecular interactions between parkin and other proteins. The studies showed higher PRKN mutation rates and lower parkin expression in high grade gliomas. Patients with higher parkin expression had better overall survival. Besides, different molecular pathways associated with parkin were described, some of them regarded as potential therapeutic targets.